A place for taxonomic profiling in the study of the coral prokaryotic microbiome. Issue 6 (2nd April 2019) - Hernandez-Agreda, Alejandra; Leggat, William; Ainsworth, Tracy D
ABSTRACT: The enormous variability in richness, abundance and diversity of unknown bacterial organisms inhabiting the coral microbiome have challenged our understanding of their functional contribution to coral health. Identifying the attributes of the healthy meta-organism is paramount for contemporary approaches aiming to manipulate dysbiotic stages of the coral microbiome. This review evaluates the current knowledge on the structure and mechanisms driving bacterial communities in the coral microbiome and discusses two topics requiring further research to define the healthy coral microbiome. (i) We examine the necessity to establish microbial baselines to understand the spatial and temporal dynamics of the healthy coral microbiome and summarise conceptual and logistic challenges to consider in the design of these baselines. (ii) We propose potential mechanical, physical and chemical mechanisms driving bacterial distribution within coral compartments and suggest experiments to test them. Finally, we highlight aspects of the use of 16S amplicon sequencing requiring standardization and discuss its contribution to other multi-omics approaches. Abstract : Authors discuss avenues to tackle two current challenges in the study of corals as meta-organisms: the characterization of microbiome natural fluctuations, and bacteria localization within the coral microhabitats.